Combined mutations in nonstructural protein 14, envelope, and membrane proteins mitigate the neuropathogenicity of SARS-CoV-2 Omicron BA.1 in K18-hACE2 mice - Kotou Sangare; Shufeng Liu; Prabhuanand Selvaraj; Charles B. Stauft; Matthew F. Starost; Tony T. Wang (mSphere)
ABSTRACT We previously reported that mutations outside the spike protein play a role in the attenuation of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron BA.1 variant in human ACE2 transgenic mice (K18-hACE2). Here, we assessed the pathogenicity of SARS-CoV-2 (WA1/2020) containing mutations from the Omicron BA.1 variant in K18-hACE2 mice. At an infection dose of 104 plaque-forming units (PFU), WA1 virus carrying Omicron BA.1 Nsp14(I42V), E(T9I), M(D3G/Q19E/A63T), but not Nsp6(Δ105–107, I189V), substitutions showed significant reduction in lethality. Interestingly, reduction of viral load is more pronounced in the brains than in the lungs. Subsequent analyses suggest that BA.1 E(T9I) and M(D3G/Q19E/A63T) substitutions result in less efficient packaging of virus-like particles. Given that Nsp14(I42V), E(T9I), M(Q19E/A63T) are well preserved in subsequent omicron subvariants, including currently circulating variants, our findings highlight the importance of understanding how non-spike mutations affect the pathogenicity of SARS-CoV-2 variants.IMPORTANCEInoculation of transgenic mice expressing human angiotensin-converting enzyme 2 (hACE2) with SARS-CoV-2 often leads to a fatal brain infection. Omicron BA.1 variant, however, was found to be non-lethal in this model. Here, we systematically assessed the effect of individual mutations of Omicron BA.1 on the pathogenicity of the virus in hACE2 transgenic mice and found that combination of 5 mutations of Nsp14, E, and M of BA.1 variant significantly lowered brain viral load and reduced lethality. These results provide new insights into how SARS-CoV-2 Omicron BA.1 is attenuated.